1096 Morning Wakefulness is Associated with Reduced Suicidal Ideation in a Nationally-Representative US Sample. (27th May 2020) - Tubbs, A; Khader, W S; Fernandez, F; Perlis, M L; Chakravorty, S; Grandner, M A
Abstract: Introduction: Nocturnal wakefulness is a unique risk factor for suicidal ideation in clinical as well as community samples. Preliminary data suggest that morning wakefulness may also be a protective factor against such thinking. However, these associations have not been explored in a nationally-representative dataset. Methods: Data were collected from the 2015-2016 wave of the National Health and Nutrition Examination Survey. Participants reported typical bedtimes and waketimes. From these values, wakefulness during the night (00:00 to 05:59), morning (06:00 to 11:59), afternoon (12:00 to 17:59), and evening (18:00 to 23:59) was determined. Suicidal ideation was assessed by a question about "thoughts that you would be better off dead, or thoughts of hurting yourself in some way." Ordinal logistic regression estimated the association between the number of hours awake at particular times of day and the frequency of suicidal ideation. Additional analyses adjusted for demographic factors and depressed mood. Results: Out of 5133 respondents with available data, 125 reported suicidal ideation several days a week, 36 reported suicidal ideation more than half the days, and 29 reported suicidal ideation nearly every day. When controlling for demographics, morning wakefulness was associated with reduced frequency of suicidal ideation (OR: 0.69, 95% CI: [0.59, 0.8]). Controlling for depressed mood attenuated, but did not eliminate, this association. Nocturnal wakefulness was not associated with suicidal ideation in this sample. Conclusion: Using data from a nationally representative sample, morning wakefulness was associated with less frequent suicidal ideation. However, previous findings regarding nocturnal wakefulness were not replicated. The limited number of individuals in the sample endorsing both suicidal ideation and nighttime wakefulness may have insufficient power to detect an association. Support: Dr. Grandner is supported by R01MD011600.